The genus Arrhopalites (Collembola, Arrhopalitidae) in Asia, with the description of two new Japanese species of Yosiis collection - Zeppelini, Douglas (Zootaxa, 2004)
The seventeen Asian species and two species from the East Europe (Moravia and Ukraine) of the genus Arrhopalites (Collembola: Arrhopalitidae) are diagnosed, discussed and compared. The Japanese species are re-described and two new Japanese epigaeic species, A. yosii sp. n. and A. ezoensis sp. n., are described and illustrated. A key for identification is given.